Increased resolution of soils information through morphon segmentation of the Korentepoort mountain catchment. Issue 4 (8th August 2021) - Malan, GJ; De Clercq, WP; Rozanov, AB; Clarke, C; Helness, H; Damman, S; Elema, N; Atkinson, J
Abstract : Recent climate instability necessitates a fresh approach to water cycle services in the Hessequa municipal region. Attention is drawn to impacts on water storage in this region, and an assessment of the current status is necessary. Land-use change and soil properties are focal points of a runoff assessment. Defining Land Type soils information is necessary to support agricultural needs, concentrating on depth-limiting materials, mechanical limitations and texture. It is evident in the area under study that mountainous regions are not well-described. With most dams located in mountain regions and the land increasingly being used for agroforestry, the demand for better supporting information has increased. Furthermore, the available Land Type polygons for the region are too coarse for the catchment, which is primarily undulated. Enhanced Land Type mapping resolution may be defined through terrain morphological segmentation. The process indicates that the terrain prediction capability is acceptable, with 62% and 74% within 4 and 15 m search windows, respectively. This information has provided a broader platform to enhance our ability to deal with the impacts of climate and land-use change in the Korentepoort mountain catchment.